Acute coronary syndrome due to midazolam use: Kounis syndrome during a transurethral prostatectomy - Ahmet Hakan Ateş; Selim Kul (KARE Publishing, 2015)
Developments in the drugs industry are leading to more rare drug side effects being encountered in clinical practice. Of these side effects, allergic reactions and hypersensitivity are seen in the usage of a large group of drugs such as antibiotics, analgesics, antineoplastics, contrast agents, corticosteroids, intravenous anesthetics, nonsteroidal anti-inflammatory drugs, and proton pump inhibitors. One important result of these reactions is acute coronary syndrome, which may have serious life-threatening results. This syndrome was first described in 1991 by Kounis as an 'allergic angina syndrome progressing to acute myocardial infarction', and thereafter called 'allergic myocardial infarction'. This case report presents a 70-year-old male who had angina and dyspnea after administration of midazolam at the beginning of a transurethral prostatectomy operation.